Virgin Olive Oil Phenolic Compounds Modulate the HDL Lipidome in Hypercholesterolaemic Subjects: A Lipidomic Analysis of the VOHF Study - Fernández‐Castillejo, Sara; Pedret, Anna; Catalán, Úrsula; Valls, Rosa‐Maria; Farràs, Marta; Rubió, Laura; Castañer, Olga; Macià, Alba; Fitó, Montse; Motilva, Maria José; Covas, Maria‐Isabel; Giera, Martin; et al. (Molecular nutrition & food research, 2021)
Scope The lipidomic analysis of high‐density lipoprotein (HDL) could be useful to identify new biomarkers of HDL function. Methods and results A randomized, controlled, double‐blind, crossover trial (33 hypercholesterolaemic subjects) is performed with a control virgin olive oil (VOO), VOO enriched with its own phenolic compounds (FVOO), or VOO enriched with additional phenolic compounds from thyme (FVOOT) for 3 weeks. HDL lipidomic analyses are performed using the Lipidyzer platform. VOO and FVOO intake increase monounsaturated‐fatty acids (FAs) and decrease saturated and polyunsaturated FAs in triacylglyceride (TAG) species, among others species. In contrast, FVOOT intake does not induce these FAs changes. The decrease in TAG52:3(FA16:0) after VOO intake and the decrease in TAG52:5(FA18:2) after FVOO intake are inversely associated with changes in HDL resistance to oxidation. After FVOO intake, the decrease in TAG54:6(FA18:2) in HDL is inversely associated with changes in HDL cholesterol efflux capacity. Conclusion VOO and FVOO consumption has an impact on the HDL lipidome, in particular TAG species. Although TAGs are minor components of HDL mass, the observed changes in TAG modulated HDL functionality towards a cardioprotective mode. The assessment of the HDL lipidome is a valuable approach to identify and characterize new biomarkers of HDL function. The sustained intake of virgin olive oil (VOO) and a functional VOO enrich with its own phenolic compounds (FVOO) modify the fatty acid profile in the high‐density lipoprotein (HDL) triacylglycerides, among others, whereas a functional VOO enrich with phenolic compounds from thyme (FVOOT) does not induce these changes. These changes are associated with changes in HDL functionality.